Identification of Stable Male Sterile Lines and Better Comnbiners For Exploitation of Hybrid Vigour in Rice (Oryza Sativa L.) - Rosamma C A (Department of Plant Breeding and Genetics, College of Horticulture, 1998)
Investigations to identify stable male sterile lines and better combiners for the exploitation of hybrid vigour in rice were conducted at College of Horticulture, Vetlantkkara and at Agricultural Research Station, Mannuthy during 1994-98. The study included evaluation of cytoplasmic - genic male sterile (CMS) lines to identify stable lines, identification of maintainers and restorers for different CMS lines, inheritance of fertility restoration, studies on the genetic distance between maintainers and restorers and genetic analysis of the hybrids. Out of the ten CMS lines evaluated, seven were identified as stable for pollen and spikelet sterility behaviour. Studies on the floral traits which influence outcrossing expressed variation between CMS lines and between seasons. Jyothi, Aruna, Pavizham and Ptb 10 produced more number of sterile hybrids when crossed with CMS lines having WA cytoplasm and hence these varieties can be used as maintainers. More number of fertile hybrid combinations were produced by Annapoorna, Matta Triveni, Kanchana, IR 36 and Aiswarya indicating the use of these varieties as restorers for WA cytoplasmic source. All the genotypes under study produced sterile hybrids when crossed with CMS lines having O. perennis cytoplasm and no restorers could be identified for this new source of cytoplasmic male sterility. Inheritance studies on fertility restoration indicated polygenic mode of inheritance for this particular character.